ANALYSIS OF FINANCIAL AND ECONOMIC INSTRUMENTS IN THE CONTEXT OF TRANSBOUNDARY COOPERATION - Verbovska , L. S.; Lugova , M.I. (The actual problems of regional economy development, 2017)
The article is devoted to the problems of efficient functioning of transboundary cooperation as the main factor of the influence of international cooperation on the development of territories included in the Carpathian Euroregion. According to the results of the study, it was established that transfrontier co-operation is of strategic importance, since international technical assistance projects and programs are a real resource and instrument that help transnational areas at the present time to be capable and contribute to improving the efficiency of government work, infrastructure, spatial planning, improvement of social protection of the population, improvement of depressed territories and integrated regional development of territories. The options of participation of border areas of Ukraine in the implementation of cross-border cooperation projects within the framework of the European Neighborhood and Partnership Instrument are considered.